(untitled) (Biodiversitas Journal of Biological Diversity, 2017)
Abd Rabou AN, Radwan ES. 2017. The current status of the date palm (Phoenix dactylifera) and its uses in the Gaza Strip, Palestine. Biodiversitas 18: 1047-1061. The date palm (Phoenix dactylifera L.) is considered one of the most important fruit crops in Palestine. It has a major socio-economic importance due to its commercial, nutritional, environmental, social, health and religious values. Because of its importance as a resistant and strategic crop facing serious local threats like pest infestation, underdeveloped marketing and mismanagement, the current study comes to investigate the status of the date palm tree and its uses in the Gaza Strip. Field surveys and institutional visits were applied to fulfill the purpose of the study. The current study revealed a total number of 250,000 trees of date palm existing in the Gaza Strip, with 40% of the dates is concentrated in the Middle Governorate. At least, 19 cultivars have been recorded locally with the ‘Hayani’, ‘Barhee’ and ’Bentaisha’ being the most common. The average date production in the last few years was 12,000 - 15,000 ton per year. More than 40 industries and uses associated with the date palm tree have been observed in the Gaza Strip, with the handicraft production and food industries are the main creative uses by the Palestinian community. Finally, the study recommends the improvement of the processes of date palm cultivation, production, protection, and marketing. The cooperation of different parties is very essential to ensure good sustainable development and uses of the date palm in the Gaza Strip, Palestine.